Cultural Acculturation and Sexual Education Reflections of Ketupat Jembut in Tegalsari City Semarang - Mukafi, Muhammad Hamdan; Gwyneth Velodyne, Abigail Clarence (Sabda: Jurnal Kajian Kebudayaan, 2024)
It is common to hear the word Ketupat, especially when celebrating Eid al-Fitir after a month of fasting during Ramadan. In the Javanese Islamic tradition, Ketupat is often interpreted as a symbol of acknowledging mistakes and asking for forgiveness. Related to this, the people of Semarang City, especially the Tegalsari area, expanded the meaning of the Ketupat by giving birth to Ketupat Jembut. Looking at the name, previous studies on Ketupat that interpret it as a sacred and holy tradition also require further understanding, especially in finding the relationship between the sacred context and the taboo and vulgar in people's views. However, this study looks at how Muslim communities in various regions perform cultural acculturation and allow a positive view of it. By conducting interviews and direct observations of the Tegalsari community, this research found several positive perspectives on the birth and running of the Ketupat Jembut tradition. The meaning of these observations relates elements of myth, arbitrary, and epistemes that arise from something vulgar, but are related to the context of sexual education and sufism. The normalization of the word jembut leads to peace of heart and purity of soul as explained about the function of sufism in sexual education. Moreover, the finding of the name Ketupat jembut also intersects with the understanding of the honor of sexuality for women as subjects and men as participants. Keywords: Ketupat jembut,myths, arbitrary, epistemes, tasawuf, sexual education